Translation Analysis of Beauty Terms in Webtoon: The Secret of Angel and Make-Up Man - Hanniarsha Alyfia; Ahmad Jum’a Khatib Nur Ali (Indonesian Journal of EFL and Linguistics, 2021)
The field of beauty every day has rapid changes, so it has many new terms growing in it. The webtoon has now expanded and has several titles translated into various languages, including Indonesian. Not only as entertainment but webtoon also indirectly brings beauty terms that do not yet have their equivalents in Indonesian. This research aims to determine how beauty terms in the webtoon are translated from English to Indonesian. This research uses a qualitative method. The source of data used is 50 chapters from two webtoons entitled The Secret of Angel (2018) and Make-Up Man (2019) in the English version and their translation in Indonesian. The results in this research indicate that based on the translation strategy theory, the translators for both of the webtoon used four different translation strategies namely: loan, unit shift, distribution change, and calque. The implication of this research is that in translating the English beauty terms into Indonesian webtoon translators often employed loan strategy by borrowing or retaining the ST items in the TT. The reasons why the translators often employ the borrowing strategy are due to the limited space in the webtoon and also because the target readers are more familiar with the original English beauty terms.